Implementation of cross-sectoral rehabilitation in the Nordic countries: a scoping review - Bøgard, Helle; Green Knakkergaard, Signe; Simonÿ, Charlotte; Tang, Lars Hermann; Christensen, Jeanette Reffstrup; Dalhoff Pedersen, Anne; Luijk, Alexander; Gundtoft Roikjær, Stine (Frontiers in Health Services, 2025)
IntroductionRehabilitation needs are rising in the Nordic countries due to an aging population and declining health profiles. Nordic healthcare systems share common features, including universal access, organization, and substantial tax-based financing. Due to the organization of the healthcare system, patients often experience transitions between sectors as part of the rehabilitation program. This fragmented setup undermines the continuity and quality of rehabilitation, making implementation more difficult. To inform future implementation processes, this scoping review examines the factors that influence cross-sectoral rehabilitation in settings with comparable healthcare systems.MethodsThis Scoping review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. The search strategy aimed to identify published, peer-reviewed primary studies on interventions implemented in adult rehabilitation within Nordic countries. Data were charted following Levac et al.'s framework and analyzed using Elo & Kyngäs' content analysis to identify factors influencing implementation. Key study characteristics and implementation approaches were synthesized narratively and in tables.ResultsThirty-six papers were identified. Most studies described the implementation of rehabilitation transitioning from the secondary to the primary sector. A top-down implementation approach was predominantly reported and appears more facilitating than a bottom-up approach. Implementation of rehabilitation across sectors is influenced by an interplay of factors: (1) Organization & Resources: alignment of context with intervention, involvement from front-line personnel, time & resources, the workplace itself, and managers, and (2) Collaboration & Communication, including knowledge and competence, attitudes, communication, patients, and families.ConclusionWhile this scoping review conveys that collaboration, communication, resources, and organization have a central role affecting the implementation of cross-sectoral rehabilitation, it further identifies knowledge gaps, such as the lack of the patients' perspective, the use of a framework or other systematic approach to ensure the success of the implementation.